Counseling on Compliance with the Use of Birth Control Pills to Couples of Childbearing Age in Neighborhood V, Baru Ladang Bambu Village in 2021 - Nurdiana Manurung; Rizk A. Bakara (Science Midwifery, 2021)
The purpose of this study was to determine the relationship between knowledge of women of childbearing age about birth control pills with adherence to the use of birth control pills. And the activities carried out are to increase the compliance of couples of childbearing age in the use of birth control pills and increase the role of couples of childbearing age in choosing contraceptives to be used. And the results of the research are To achieve the objectives of the above activities, activities are carried out, including the delivery of material about contraceptives which is an effort to help couples of childbearing age to comply with the use of birth control pills.